Invisible - Grant, Andrew 1968- (New York : Ballantine Books, 2019)
"An Army veteran and intelligence agent goes undercover as a janitor at a federal courthouse to pursue his own brand of justice in a thriller that's part John Grisham, part Robert Crais."--Publisher's description.
Keywords: Murder -- Fiction -- Investigation; Fathers and sons -- Fiction; FICTION / Suspense; FICTION / Action & Adventure; Suspense fiction; Thrillers (Fiction)